2021
DOI: 10.1111/jfbc.13877
|View full text |Cite
|
Sign up to set email alerts
|

Lycoperoside H, a steroidal alkaloid saponin in tomato seeds, ameliorates atopic dermatitis‐like symptoms in IL‐33 transgenic mice

Abstract: Tomato seeds contain steroidal saponins called lycoperosides. However, it currently remains unclear whether lycoperosides exert anti‐inflammatory or anti‐allergic effects. Therefore, we herein investigated the effects of tomato seed extract (TSE) and lycoperoside H (LH) in Interleukin (IL)‐33 transgenic mice. TSE (500 mg/kg) or LH (10 mg/kg) was orally administered once a day for 101 days and then evaluated mouse behavior, skin symptoms, and blood and skin inflammatory cytokines. TSE slightly suppressed scratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Taken together, it is suggested that lycoperoside H (3) improved TEWL by acting as a partial glucocorticoid receptor agonist with suppression of the acute inflammatory effect. This activity is also considered to be the mechanism of our previous results, which demonstrated that oral administration of lycoperoside H suppressed AD-like skin inflammation in IL-33 transgenic mice [10].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Taken together, it is suggested that lycoperoside H (3) improved TEWL by acting as a partial glucocorticoid receptor agonist with suppression of the acute inflammatory effect. This activity is also considered to be the mechanism of our previous results, which demonstrated that oral administration of lycoperoside H suppressed AD-like skin inflammation in IL-33 transgenic mice [10].…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, tomato seed saponins (1-4,6-8), especially lycoperoside C (2), significantly upregulated the mRNA expression of these enzymes in HaCaT cells. On the other hand, tomato seed flavonoids (5,(9)(10)(11) exhibited a trend to downregulate the expression of enzymes for ceramide synthesis. These results suggest that tomato seed saponins appeared to be leading candidates that contribute to epidermal hydration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Locules are divided by a septum, with seeds bound to an elongated axial placenta [ 61 ]. Tomato seeds are known to contain steroidal saponins called lycoperosides, particularly lycoperoside H, which are believed to exert anti-inflammatory effects [ 62 , 63 ].…”
Section: Tomato Constituents For Healthmentioning
confidence: 99%
“…Thus, we performed a constituent study of tomato seeds to find effective use of waste resources and found that lycoperosides are major saponins in the seeds. Furthermore, lycoperoside H was found to suppress atopic dermatitis-like skin inflammation in IL-33 deficient mice [33]. Despite the above chemical and preclinical studies of tomato saponins, there are no reports of a clinical study of saponins especially on the skin condition.…”
Section: Introductionmentioning
confidence: 99%